PEMANFAATAN BAKTERI ANTAGONIS LUMPUR SIDOARJO UNTUK MENEKAN Sclerotium rolfsiiSACC. PENYEBAB PENYAKIT REBAH SEMAI PADA TANAMAN KEDELAI - Arriani, Intan Fuji (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2019)
ABSTRACT Soybean plants is a strategic commodity in Indonesia, because soybean is an important crop food after rice and maize. One of the important diseases that attack soybean plants is damping off caused by pathogenic fungi S. rolfsii. One effort to suppress attack from pathogenic fungi it S. rolfsii attack is by using biological agents. Trial of antagonistic bacteria with fungi S. rolfsii stepin vitro is test the artificial media (media NA). The result of the selection of the lumpur Sidoarjo bacterial isolates obtained 15 and 5 bacteria have antagonistic properties against pathogenic fungi S. rolfsii is isolates LUSI 93, LUSI 43, LUSI 16, LUSI 6, and LUSI 54. The identification and characterization of antagonistic bacteria lumpur Sidoarjo is LUSI 93 belongs to the genus Vibrio sp. And for LUSI 54, 16 LUSI, LUSI 43, and LUSI 6 has been identified by previous research in a row belongs to the genus Corynebacterium sp, Vibrio sp, Erwinia sp and Corynebacterium sp.